2016
DOI: 10.1016/j.virol.2016.09.014
|View full text |Cite
|
Sign up to set email alerts
|

Rhesus rotavirus VP6 regulates ERK-dependent calcium influx in cholangiocytes

Abstract: The Rhesus rotavirus (RRV) induced murine model of biliary atresia (BA) is a useful tool in studying the pathogenesis of this neonatal biliary obstructive disease. In this model, the mitogen associated protein kinase pathway is involved in RRV infection of biliary epithelial cells (cholangiocytes). We hypothesized that extracellular signal-related kinase (ERK) phosphorylation is integral to calcium influx, allowing for viral replication within the cholangiocyte. Utilizing ERK and calcium inhibitors in immortal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 55 publications
0
7
0
Order By: Relevance
“…Interestingly, blocking SOCE in HIEs significantly reduced the Ca 2+ spikes, but the effect was less pronounced than in MA104 cells, suggesting other pathway(s) may exist that support RV-induced Ca 2+ spikes in HIEs. Further, RV can also infect other cell types, including monocytes and macrophages, hepatocytes, cholangiocytes, and enteroendocrine cells, all of which express a different repertoire of Ca 2+ channels 51,5456 . Thus, characterizing the nature of RV-induced Ca 2+ signaling in these cell types will help elucidate whether these signals are involved in diseases caused by RV.…”
Section: Discussionmentioning
confidence: 99%
“…Interestingly, blocking SOCE in HIEs significantly reduced the Ca 2+ spikes, but the effect was less pronounced than in MA104 cells, suggesting other pathway(s) may exist that support RV-induced Ca 2+ spikes in HIEs. Further, RV can also infect other cell types, including monocytes and macrophages, hepatocytes, cholangiocytes, and enteroendocrine cells, all of which express a different repertoire of Ca 2+ channels 51,5456 . Thus, characterizing the nature of RV-induced Ca 2+ signaling in these cell types will help elucidate whether these signals are involved in diseases caused by RV.…”
Section: Discussionmentioning
confidence: 99%
“…Among the three central members of the MAPK pathway, extracellular signalregulated kinase (ERK) 1/2 and p38 activation play the most important roles in RRV infection of cholangiocytes as they seem to be involved in both viral replication and epithelial injury (69). Further studies revealed that ERK phosphorylation and calcium influx appear to be essential to RRV infection, and RRV's viral protein 6 (VP6) drives ERK phosphorylation (70).…”
Section: Cholangiocyte Immunobiologymentioning
confidence: 99%
“…https://doi.org/10.1101/562421 doi: bioRxiv preprint Rhesus and group A rotaviruses also activate MAPK/ERK pathway to facilitate viral replication 338 and viral uncoating, respectively(66, 67). https://doi.org/10.1101/562421 doi: bioRxiv preprint Rhesus and group A rotaviruses also activate MAPK/ERK pathway to facilitate viral replication 338 and viral uncoating, respectively(66, 67).…”
mentioning
confidence: 99%